2020
DOI: 10.1002/slct.202003903
|View full text |Cite
|
Sign up to set email alerts
|

Atom‐economical Approaches to 1,5‐Benzodiazepines Containing Indole Ring via Fe3O4@SiO2‐PTSA‐catalyzed Multi‐component Domino Reactions

Abstract: Four novel atom-economical approaches for synthesis of 1,5dihydrospiro[benzo[b][1,4]diazepine-2,3'-indole] compounds via three-component or four-component domino reactions have been developed in the presence of a catalytic amount of magnetic nanoparticles (Fe 3 O 4 @SiO 2-PTSA) in ethanol, which provide an efficient one-pot synthesis of 1,5-benzodiazepines with multi-ring system and functional groups containing indole, aryl, ester, acyl and alkyl groups in excellent yields. In a one-pot operation, two new nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Imine intermediates would be activated by the chiral phosphoric acids via hydrogen bonds. The Wang group [16c] described a similar reaction by using Fe 3 O 4 @SiO 2 ‐PTSA as the catalyst. Pardasani group [16d] reported the solvent‐free synthesis of spiro‐benzimidazoquinazolinones from reactions of 2‐aminobenzimidazole.…”
Section: Reactions Of C3 Carbonyl Groupmentioning
confidence: 99%
“…Imine intermediates would be activated by the chiral phosphoric acids via hydrogen bonds. The Wang group [16c] described a similar reaction by using Fe 3 O 4 @SiO 2 ‐PTSA as the catalyst. Pardasani group [16d] reported the solvent‐free synthesis of spiro‐benzimidazoquinazolinones from reactions of 2‐aminobenzimidazole.…”
Section: Reactions Of C3 Carbonyl Groupmentioning
confidence: 99%
“…Zhang et al 89 reported three different three-component reactions for the synthesis of 1,5-BZDs ( 33 ) containing a indole ring introduced by Fe 3 O 4 @SiO 2 -PTSA as a magnetic nanocatalyst in EtOH. All reactions involved two common components, namely, OPD ( 1 ) and isatin ( 30 ), but the third component was ethyl acetoacetate ( 31 ) or 3-butyne-2-one ( 32 ) or benzoylacetone ( 14 ) and gave product ( 33 ).…”
Section: Synthetic Approaches Of Bzdsmentioning
confidence: 99%
“…Zhang and colleges 89 developed an efficient method for the synthesis of BZDs ( 33 ) using substituted OPD ( 1 ), N , N -dimethylformamide dimethylacetal ( 44 ), aromatic acetone ( 10 ) and isatin ( 30 ) in ethanol at reflux to RT. The authors obtained 10 new compounds ( 33 ) in 5–12 h in 79–90% yield using various aromatic ketones and substituted OPD.…”
Section: Synthetic Approaches Of Bzdsmentioning
confidence: 99%
“…This step is generally realized in the presence of a catalyst. A large number of synthetic methodologies for 1,5-benzodiazepines in the existence of distinct single-acid catalysts, such as trifluoroacetic acid, 29,30 p -toluenesulfonic acid, 31–33 polyphosphoric acid, 34 heteropoly acids, 35,36 Ce(OTf) 3 (ref. 37) and Cu(OAc) 2 (ref.…”
Section: Introductionmentioning
confidence: 99%